Gold-Catalyzed organic reactions - Hashmi, A. Stephen K. (Inventing reactions, 2013)
Although homogeneous gold catalysis was known previously, an exponential growth was only induced 12 years ago. The key findings which induce that rise of the field are discussed. This includes early reactions of allenes and furanynes and intermediates of these conversions as well as hydroarylation reactions. Other substrate types addressed are alkynyl epoxides and N-propargyl carboxamides. Important vinylgold intermediates, the transmetalation from gold to other transition metals, the development of new ligands for gold catalysis, and significant contributions from computational chemistry are other crucial points for the field highlighted here.
First online: 01 August 2012
Gesehen am 22.02.2022